Implementation of 5R Culture to Achieve Total Quality Management (TQM) at PT Aneka Dharma Persada - Budiman, Rizki; Abma, Vendie; Noviandhini, Ramadhena Putri Ayu; Wibowo, Rangga Pangestu (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
The concept of 'quality' is becoming increasingly recognized across industrial sectors, as evidenced by the emergence of methodologies such as TQM, Kaizen, and Quality Circles. The 5R (Reduced, Refined, Radiant, Retain, Reliable) program, which includes Sort, Set in Order, Shine, Standardize, and Sustain, has become an essential component in enhancing efficiency and quality management within a company. This study aims to evaluate the effectiveness of the 5R program implementation on the achievement of Total Quality Management (TQM). The method of this study is a descriptive approach using a case study design and mixed methods, integrating both qualitative (field observations and interviews) and quantitative data (audit scores and monthly performance metrics). This combination enables a comprehensive evaluation of the 5R program. Data were collected through field observations, in-depth interviews, analysis of audit results, and monthly performance scores from ten work areas. Manufacturing company PT ADP, as a case study, was employed to examine the benefits of the 5R implementation in relation to TQM standards. The findings contribute to practical knowledge by demonstrating that structured implementation of 5R can significantly support Total Quality Management (TQM) in manufacturing settings, particularly in enhancing productivity, discipline, and operational efficiency. The results indicate that the 5R program can support the foundation of TQM by ensuring higher work efficiency, reduced waste, and a more disciplined and responsible work ethic. The 5R culture is essential in supporting the implementation of TQM to improve quality and innovation for sustainable growth, competitiveness, adaptability, and customer satisfaction